Influence of Seaweed Liquid Fertilizer on the Growth of Trigonellafoenum-graecum L. - Sujatha, Muthuswamy; Pradeepa, Varadharajaperumal; Mahalakshmi, Arumugasamy (Asian Journal of Biological and Life Sciences)
The effect of seaweed liquid fertilizer (SLF) of Sargassum wightii on germination, growth and biochemical constituents of Trigonellafoenum-graecum L. (Fenugreek) was studied. Sargassum wightii was collected from Kanyakumari (longitude 8.0883° N, latitude 77.5385° E) for the present study. Different concentrations (2%, 4%, 6%, 8% and 10%) of SLF were prepared using distilled water. Maximum germination percentage (100 ± 0.00%), fresh weight (3.63±0.18 g), dry weight (0.22±0.04 g), shoot length (6.83 ± 1.04 cm), root length (3.26 ± 0.20 cm), recorded at 6% concentration of Sargassum wightii liquid fertilizer treated fenugreek. Pigments such as total chlorophyll (11.95±0.22 mg.g/fr.wt) and carotenoids (4.9±0.1 mg.g/fr.wt) contents in leaves recorded at 6% SLF were the highest. The 6% SLF treated seedling showed the highest content of protein (6.8±0.1mg.g/fr.wt), aminoacid (3.63 ± 0.05mg.g/fr.wt), carbohydrate (2.6 ± 0.1 mg.g/fr.wt), ascorbic acid (0.36±0.015 mg.g/fr.wt), phenol (0.8±0.01 mg.g/fr.wt), nitrate (9.96± 1.35 mg.g/fr.wt) and nitrate reductase (14.96±0.85 mg.g/fr.wt) activity of shoots and roots respectively. The SLF showed better responses at lower concentration when compared to control and higher concentrations showed declining trend. The present study demonstrated that Sargassum wightii liquid extract could serve as an alternative biofertilizer as it is eco-friendly, cheaper, deliver substantial economic and environmental benefits to farmers.
Keywords: Brown seaweeds; Germination and Growth; Sargassum wightii; Seaweed liquid fertilizer; Trigonellafoenum-graecum